A sustainable production of lignocellulolytic enzymes and value added metabolites from banana pseudostem waste by Bacillus wakoensis NAULH-4. (June 2021) - Patel, Hiren; Khimani, Mehul; Vekariya, Rohit; Mahatma, Lalit
Graphical abstract: Highlights: Decay lignocellulosic waste is a source of diversified potential microbes. Phenotypic Microarray analysis fleeting the study of metabolic pathway of microbes. Genomic approaches used for lignocellulolytic enzymes gene activity. Different parameters applied to optimize maximum degradation rate of BP. Resourceful transformation of BP waste in to valuable metabolites. Abstract: The most plentiful carbohydrate present on earth is in the form of cellulose which has a tremendous capacity to manufacture second or third-generation biofuels and other valuable metabolites. Cellulose is a significant part of banana pseudostem (BP) squander that causes numerous environmental issues. Hence, disposal of BP is nowadays a major obstacle for Indian farmers because of immense volume, delay in decay raise in a foul smell during debasement which attracts pests and insects to farm. The present study reports the identification of potential isolates, which efficiently debase BP. Out of many isolates, NAULH-4 showed the uppermost decomposition rate of cellulose, hemicellulose, and lignin at 45 °C and pH 8 up to 28 days incubation. Moreover, the taxonomic characterization using phenotypic microarray (PM) technology directs that the isolate NAULH-4 belongs to Bacillus with 0.71 SIM index in metabolic pathway network which is reinforced by 16 s rRNA analysis. Molecular data reveal that NAULH-4 contain laccase, xylanase, and cellulase gene. Overall, Bacillus wakoensis NAULH-4 can be applicable for promising microbe for the conversion of BP waste into value-added metabolites.